Students' Challenges in Writing Personal Letter - Yelvi Rahmadani; Nora Fudhla (Journal of English Language Teaching, 2022)
The Corona Virus Disease (Covid-19) pandemic has spread all over the world including Indonesia. There are many aspects affected by this virus, one of which is educational activities. Education in Indonesia has a big change caused by this virus. Schools or educational facilities have to close to prevent the spread of this virus. So that, the students cannot come to classroom and they have to run online learning.  This research aimed to find out the challenges faced by eleventh grade students of SMA Pertiwi 1 Padang in writing personal letter during online learning. This research is a descriptive research. The samples of this research were 157 students of eleventh grade students of SMA Pertiwi 1 Padang, where the samples were selected by using proportional random sampling technique. The technique of data collection was using questionnaire. The students were given 24 questions related to process of writing, aspects of writing, gen                                                                                                            eric structure of personal letter and language features of personal letter to find out their challenges in writing personal letter during online learning. The result showed that mostly the students have challenges in writing personal letter during online learning. It can be proved from the result of this study where the mean score of process indicator was 2.72, the mean score of aspect of writing indicator was 2.78, the mean score of generic structure of personal letter was 2.65 and the mean score of language features of personal letter was 2.75. The highest mean score was 2.78 in the aspect of writing, which was in the difficult category. So, the students’ challenges in writing personal letter during online learning were in difficult category.